La comunidad de los otros. A partir de Jean-Luc Nancy - Caldarone, Rosaria (THÉMATA. Revista de Filosofía, 2013)
El tema de la “comunidad” es central desde el punto de vista antropológico, ético y filosófico-político. A partir de los años 80 se despliega un debate en el pensamiento francés, y ya en los 90 son autores italianos los que participan en él. La posible-imposibilidad de lo común es una temática de gran profundidad, tratada por estos pensadores en su particular dialéctica. El artículo pone el acento en Jean-Luc Nancy, pero hace dialogar a Badiou, Lacoue-Labarthe, Agamben, Blanchot, Jabès, Esposito, Derrida, y –en forma particular- a Platón. The topic of the “community” has a fundamental relevance from the anthropological, ethical and political point of view. Starting from the years ’80 in France, and then during the ’90 in Italy, the debate has been developed in a very vivid manner. The possible-impossibility of the “community” is a very profound subject that has been treated in a particular dialectical manner by these authors. The article emphasizes the contribution of Jean-Luc Nancy, putting his thought in dialog with Badiou, Lacoue-Labarthe, Agamben, Blanchot, Jabès, Esposito, Derrida and –in a very deep manner- Plato.